Sie sind auf Seite 1von 8

Partial Differential Equations, 2nd Edition, L.C.

Evans
Chapter 5 Sobolev Spaces

Shih-Hsin Chen, Yung-Hsiang Huang

2017.08.13

1. Proof. We prove the case k = 0 for simplicity. The general case is almost the same (except we
need the standard convergence theorem between {fn } and {Dfn }).

Given a Cauchy sequence {fn } C 0, (U ), then there is a f C(U ) such that fn f uniformly
and a constant M > 0 such that for each n N and s 6= t,

|fn (s) fn (t)|


M.
|s t|

Then for each s 6= t, there is some N = N (s, t) N such that

|f (s) f (t)| |f (s) fN (s)| + |fN (s) fN (t)| + |fN (t) f (t)|

2|s t| + M |s t| .

Therefore, f C 0, (U ). It remains to show fn f in C 0, (U ). For each s, t U and  > 0,


by Cauchys criteria, we can find a N = N () such that for k, n N

|fk (s) fn (s) fk (t) + fn (t)| |s t|

For each > 0, we can find a K = K(, s, t) > N , such that |f (x) fK (x)| for x = s, or
x = t. Therefore, for every n N

|f (s)fn (s)f (t)+fn (t)| |f (s)fK (s)|+|fK (s)fn (s)fK (t)+fn (t)|+|f (t)fK (t)| 2+|st| .

Letting 0, we obtain that |f (s) fn (s) f (t) + fn (t)| |s t| for all n N ().

Department of Math., National Taiwan University. Email: d03221002@ntu.edu.tw

Department of Math., National Taiwan University. Email: d04221001@ntu.edu.tw

1
|u(x) u(y)|
2. Proof. kukC 0, = sup |u(x)| + sup .
|x y|
Set t s.t. (1 t) + t = . Then
 1t  t
|u(x) u(y)| |u(x) u(y)| |u(x) u(y)|
= .
|x y| |x y| |x y|
1t
kukC 0, kuk1t t t 1t t 1t t
kuk + [u]C 0, [u]C 0,1 := a1 b1 + a2 b2 .

Since y = xt , 0 < t < 1, is a concave function, we have


 
1t t 1t t a1  b 1  t a2  b 2  t
a1 b1 + a2 b2 = (a1 + a2 ) +
a1 + a2 a1 a1 + a2 a2
 t
b1 b2
(a1 + a2 ) +
a1 + a2 a1 + a2
= (a1 + a2 )1t (b1 + b2 ).

Then

1t
kukC 0, kuk1t t t
kuk + [u]C 0, [u]C 0,1

(kuk + [u]C 0, )1t (kuk + [u]C 0,1 )t


1t t
= kukC 0, kukC 0,1 .

Remark 1. There is a general convexity theorem for Higher-order Holder norm (due to
Hormander), see Helms [3, chapter 8].

3. Omit.

4. Proof. (b) follows easilyZfrom (a) and Holder inequality. For (a), denote the weak derivative of
t
u by u0w . Define v(t) = u0w (s) ds, then v is absolutely continuous. Given Cc ,
0
Z 1 Z 1 Z x Z 1
0
[v u] dx = u0w (t) dt0 (x) dx u(x)0 (x) dx
0
Z0 1 Z0 1 Z 01
= 0 (x) dxu0w (t) dt + u0w (x)(x) dx
0
Z 1t Z 1 0
= (t)u0w (t) dt + u0w (x)(x) dx = 0.
0 0

(This argument avoids the use of the Lebesgue Differentiation theorem if we only want to show
the 1-d weakly differentiable function F = H a.e., an absolutely continuous function.) We are
done if we use Exercise 11. (There are many other way to prove the second fundamental lemma
of calculus of variations without using mollifications. We also note such statement is true for
distributions.)

2
5. Proof. For any V W U , we can find a smooth function u such that u 1 on V and
1
supp(u) W . Take = dist(V , W c ) > 0. Let  (z) be the standard mollifier supported in
3
{|z| }, V 0 := {z : dist(z, V ) < } and
Z Z
u(x) := V 0 (x) = V 0 (x y) (y) dy = (y) dy.
Rn xV 0

Then u is smooth (by LDCT), u = 1 on V and supported in {dist(x, V ) 2} W .

6. Apply Exercise 5. We omit it since it can be found in many Differential Geometry textbooks.

7. Proof.
Z Z
p
|u| dS |u|p dS
U ZU
= div (|u|p ) dx
ZU
= |u|p div + (|u|p ) dx
U

8. Proof. Consider un (x) = h1 n dist(x, U )i+ . Note that un C(U ) , 0 un (x) 1 and
{un (x)} is decreasing to 0 for each x U , MCT tells us kun kp,U 0. On the other hand,
kun kp,U = k1kp,U is a positive constant. Hence
kT un kp,U kun kp,U
=
kun kp,U kun kp,U

which means T will not be bounded, if T exists.

9. Proof. Given u H 2 (U ) H01 (U ), there exists uk C (U ) with uk u in H 2 (U ), and


vk Cc (U ) with vk u in H 1 (U ). Hence {uk } and {uk } are bounded in L2 . Note
Z Z Z Z
uk 2
uk dS = div (uk uk ) dx = |uk | dx + uk uk dx.
U n U U U
Z Z
2
The right-hand side tends to |u| dx + uu dx. Note
U U
Z Z
uk
uk dS = div ((uk vk )uk ) dx
U n
ZU
= (uk vk )uk + (uk vk )uk dx.
U

which tends to 0 by Holder and (uk vk ) 0 in H 1 (U ) . Therefore, for all u H 2 (U ) H01 (U ),


Z
|u|2 + uu dx = 0
U

Then we apply Holders inequality to get the desired inequality.

3
10. Proof. (Sketch) (b) is similar to (a). To prove (a), we start with the formula in Hint, do
p
integration by parts once, and then apply the generalized Holder with exponents pair (p, p, p2 ).

11. Proof. Given K U , compact. Then u L1 (K). Note that the weak derivative D(u  ) =
Du  = 0. Since U is connected and u  is smooth, u is a constant c which will
converges to u in L1 (K) as  0 and hence {c 1 }
n=1 forms a Cauchy sequence (note that K
n

has finite measure) that will converges to some constant c. Therefore, u = c a.e. in K and
hence in U .

12. Proof. Consider in R1 , let u(x) = (0,1) (x).



13. Proof. Consider U = B(0, 1) {(x, y) x > 0} in R2 , let u(x, y) = r in polar coordinate.
 
1
14. Let n > 1. Show that log log 1 + |x| W 1,n (B1 (0)).

Proof.
Z Z 1
1  n
rn1 dr, let t = 1

n
|u(x)| dx = n log log 1 +
U
r r
Z0 n
1 | log log(1 + t)|
= n dt
1 tn t
| log log(1 + t)|n | log log(1 + t)|n
Since lim = 0, there is T > 0 such that < 1 for t T . Then
t t t
Z
1 | log log(1 + t)|n
Z
n
|u(x)| dx = n dt
U 1 tn t
Z T Z
1 | log log(1 + t)|n 1
n n
dt + n dt < .
1 t t 1 tn
On the other hand, we omit the proof that the first weak derivative of u exists and
1 1 xi
u xi = 1 1 .
log(1 + |x|
) 1 + |x| |x|3

So
Z Z 1
n
1 1 1 n1 1
|uxi |n dx n
log(1 + 1 ) 1 + 1 r2 r
dr, let t =
U 0 r r
r
Z
1 1
= n n
n
tn1 dt
| log(1 + t)| (1 + t)
Z1
n 1 1
n
sn esn ds (s = log(1 + t))
n log2 s e
< .

4
15. Proof. Applying Poincare inequality,
Z  12 Z  21 Z  12
2
u dx (u)2U dx + |u (u)U | dx 2
U U U
Z  12
1
|(u)U ||U | + C 2 |Du|2 dx .
U

Applying Holider inequality,


Z
1
|(u)U | |u| dx
|U | {u6=0}
Z  12  Z  21
1
12 dx u2 dx
|U | {u6=0} {u6=0}
Z  21
1 1
2
= (|U | ) 2 u dx .
|U | U

Therefore, s
Z  12 Z  12 Z  21
2 |U | 2 2
u dx u dx +C |Du| dx ,
U |U | U U
q
|U |
Since 0 |U |
< 1, we proved the desired inequality

 s  Z  12 Z  12
|U | 2 2
1 u dx C |Du| dx .
|U | U U

Remark 2. For further discussions on Poincare-Type inequality, see G.Leoni [4, Section 12.2]
and L.Tartar [6, Section 10-11].

16. Proof. For any u Cc (Rn ),


Z Z  
x 2 x
2
2uu dx = u div dx, by Divergence theorem
Rn |x| Rn |x|2
n2
Z
= u2 dx.
Rn |x|2

The Holders inequality implies that

n2
Z
u2  Z u2  12  Z  21
2
2
dx 2
dx |u| dx .
2 Rn |x| Rn |x| Rn

Given u H 1 (Rn ), there exists a sequence uk Cc (Rn ) converging to u in H 1 . By picking a


further subsequence, we may assume uk converging to u pointwisely. Fatous lemma implies

(n 2)2 u2k (n 2)2 u2


Z Z Z Z
2 2
|u| dx = liminf |uk | dx liminf 2
dx 2
dx.
Rn k Rn k 4 Rn |x| 4 Rn |x|

5
Remark 3. This proof is simpler than the one suggested in the hint. Also note that the same
approximation argument should be applied at the end of the proof to Theorem 7 on page 296.

Remark 4. A family of inequalities that interpolate between Hardy and Sobolev inequalities
is given by the Hardy-Sobolev inequality,
! p2
|u|p
Z Z
n n2 p
dx C(p) |u|2 dx
Rn |x| 2 Rn

for any u Cc (Rn ), where 2 p 2n/(n 2), n 3. One huge extensions and improvements
of the Hardy-Sobolev inequalities is the Caffarelli-Kohn-Nirenberg inequalities established in
their well-know paper [1]. See also a further generalization by C.S.Lin [5].

17. Proof. For 1 p < , there is a sequence um W 1,p C (U ) such that um u in W 1,p .
Then Z Z
p 0 p
|F (um ) F (u)| sup|F | |um u|p 0, as m .
U U
Z Z Z
0 0 0
p
|F (um )Dum F (u)Du| sup|F | |Dum Du| + p
|F 0 (um ) F 0 (u)|p |Du|p .
U U U
Up to a subsequence, we know um converges to u a.e. Since F is continuous, F 0 (um ) converge
0

to F 0 (u) a.e. Hence the last integral tends to 0 by the dominate convergence theorem. Conse-
quently, {F (um )} and {F 0 (um )Dum } converge to F (u) and F 0 (u)Du in Lp . By the uniqueness
of weak derivative, D[F (u)] = F 0 (u)Du.

On the other hand, F (u) Lp since |F (u)| kF 0 k |u| + |F (0)|.

Remark 5. Note that the hypothesis U is bounded is only used to show F (u) Lp . Such
restriction can be removed if we know F (0) = 0. (Still need F 0 L .) A trivial counterexample
for unbounded U and F (0) 6= 0 is F 1.

18. Proof. (a) and (c) follow from (b), (b) is proved by the method given in the hint easily. Note
that U can be unbounded. (See the remark for problem 17.)

19. Proof. Let be a smooth, bounded, nondecreasing function, such that 0 is bounded and
(z) = z, if 1 z 1. Let u (x) := (u/). Since u L2 , u is finite a.e. Therefore u 0
as  0 a.e.. Moreover by the mean-value theorem, for a.e. x

u (x)2 = 2 |(u(x)/) (0/)|2 sup(0 )2 u(x)2 L1

Hence u 0 in L2 by dominated convergence theorem. By exercise 17, {Du } = {0 (u/)Du}


is bounded on L2 . Given w Cc (U ),
Z Z

(Du )w = u Dw 0, since ku kL2 0
U U

6
Apply the density argument with the help of boundedness of {kDu kL2 }, we know the above
is true for any w L2 . Take w = (Du){u=0} L2 , we see
Z Z Z
2 0
|Du| = (u/)Du Du = Du (Du){u=0} 0, as  0
{u=0} {u=0} U

which is the desired result.

Remark 6. For Fractional Sobolev Space, we define


Z
2
kukH s (Rn ) = (1 + ||2 )s |u()|2 d, for s R.
Rn

which is different from Evans definition. This definition works for negative power s.

20. (Sobolev Lemma)


Proof. Since u H s L2 , Fourier inversion formula on L2 implies that u(x) = u(x) in L2
sense. However
Z Z h s
i2  21  Z h i2  12
2 2 2s
|u()| d (1 + || ) |u()| d
2 (1 + || ) d
Rn Rn Rn
Z  12
= kuk2H s (Rn ) (1 + ||2 )s d Ckuk2H s (Rn ) , since 2s > n,
Rn

we know u L1 , and the inversion formula holds pointwisely now, this tells us that for each
x Rn Z
1
|u(x)| |eix ||u()| d Ckuk2H s (Rn )
(2)n/2 Rn

Remark 7. Its true that for s = k + + n2 , 0 < < 1, H s is continuously embedded in C k, .

Remark 8. The converse of Sobolev lemma is true: If H s is continuously embedded in C k ,


then s > k + n2 . The proof is sketched in Folland [2, page 195].

21. (H s is an algebra if s > n/2)

We need the following convolution identity for Fourier transform on L2 (Rn ) :

cv = (2)n/2 u v, u, v L2 .
Lemma 9. u

Proof. Since s 0,

s/2 s/2
(1 + ||2 )s/2 1 + | | + ||)2 (1 + 2| |2 + 2||2

2s (1 + | |2 )s/2 + (1 + ||2 )s/2 .


 

7
Hence
Z Z
2
kuvk2H s = 2 s
(1 + || ) |c 2
uv()| d (2) n
(1 + ||2 )s/2 (|u| |v|)() d
Rn Z Z
2
(1 + | |2 )s/2 + (1 + ||2 )s/2 |u( )||v()| d d
 
C(n, s)
Z Z Z
2
(1 + | | ) |u( )||v()| d + (1 + ||2 )s/2 |u()||v( )| d d
2 s/2
 
=C
Z
2C (|his u| |v|())2 + (|u| |his v())2 d, where hxi := (1 + |x|2 )1/2 .

C k < >s uk2L2 kvk2L1 + kuk2L1 k < >s vk2L2 , by Youngs inequality .


Ckuk2H s kvk2H s , since kvk CkvkH s

Acknowledge
The authors would like to thank Tommaso Seneci for his/her reminder that the original proof for
problem 19 is wrong. (2017.08.12)

References
[1] Luis Caffarelli, Robert Kohn, and Louis Nirenberg. First order interpolation inequalities with
weights. Compositio Mathematica, 53(3):259275, 1984.

[2] Gerald B Folland. Introduction to Partial Differential Equations. Princeton university press,
2nd edition, 1995.

[3] Lester L Helms. Potential Theory. Springer Science & Business Media, 2nd edition, 2014.

[4] Giovanni Leoni. A first course in Sobolev spaces, volume 105. American Mathematical Society
Providence, RI, 2009.

[5] Chang Shou Lin. Interpolation inequalities with weights. Communications in Partial Differ-
ential Equations, 11(14):15151538, 1986.

[6] Luc Tartar. An introduction to Sobolev spaces and interpolation spaces, volume 3. Springer
Science & Business Media, 2007.